The Trump survival guide everything you need to know about what you hoped would never happen - Stone, Gene 1951- (Dey St., 2017)
The stunning election of Donald J. Trump rocked an already divided America and left scores of citizens, including the nearly sixty-five million voters who supported Hillary Clinton, feeling bereft and powerless. This guide offers invaluable guidance and concrete solutions they can use to make a difference in this serious call-to-arms, showing them how to move from anger and despair to activism
Keywords: Politik; USA; Trump, Donald / 1946-; Presidents / United States / Election / 2016; United States / Politics and government / 2009-